Feature‐based recursive observer design for homography estimation and its application to image stabilization. Issue 4 (17th January 2019) - Hua, Minh‐Duc; Trumpf, Jochen; Hamel, Tarek; Mahony, Robert; Morin, Pascal
Abstract: This paper presents a new algorithm for online estimation of a sequence of homographies applicable to image sequences obtained from robotic vehicles equipped with vision sensors. The approach taken exploits the underlying Special Linear group structure of the set of homographies along with gyroscope measurements and direct point‐feature correspondences between images to develop temporal filter for the homography estimate. Theoretical analysis and experimental results are provided to demonstrate the robustness of the proposed algorithm. The experimental results show excellent performance and robustness even in the case of very fast camera motions (relative to frame rate) and severe occlusions.